(untitled) (Physical Education, Health and Social Sciences, 2026)
Diabetes Mellitus (DM) is a metabolic condition characterized by persistent high blood sugar levels resulting from impaired insulin secretion. Diabetes mellitus disrupts the metabolism of lipids, carbohydrates, and proteins. The global prevalence of diabetes mellitus is steadily rising, estimated to reach 552 million by 2030. This is the cross- sectional survey study conducted at the District Headquarter Hospital KDA Kohat in Khyber Pakhtunkhwa . Detailed data regarding the age and gender of the patients were gathered, and blood glucose levels were determined using the Glucose oxidase test. The study revealed an overall diabetes mellitus (DM) prevalence of 51.4% with the higher prevalence in females (52%) than in males (48%) . Furthermore, individuals in the age group of 30-40 years were the most effected. Elevated fasting sugar (FBS) levels were observed in the age group of 10-20 years. While Random blood sugar (RBS) levels were more common in individuals aged 40 years and above.